Performance Evaluation of Paid Parking at Cilebut Station - Syaiful, Syaiful; Suherman, Suherman (Universitas Ibn Khaldun Bogor, 2024)
This study intends to find out the capacity of parking needs managed by PT. Kereta Api Indonesia (Persero) with the location of the Cilebut station research, this study used the SRP method of characteristics (Volume, Accumulation, Duration, Turnover, Index), in this study was the management of paid parking performance. Data collection was carried out using the survey method with a time of 12 hours and running for sixteen days, with the aspects taken being data on the hours of entry and exit of the vehicle to find out the characteristics of the parking. The results of this study show that the parking performance cannot accommodate motorcycle vehicles the area with an area of 486m2 has a parking capacity of 120 SRP, while the results of the study getting an index figure of more than 100% indicates too high parking performance and so turn over parking by 181% at peak hours. The result of the SRP needs that must be provided by the management with the results of the study is 159 slots to accommodate motorcycle vehicles, with an SRP value of 159 slots will produce good parking performance, namely parking according to the slots that have been provided so that motorcycle vehicle users feel safe when parking the vehicle.